Comparative evaluation of the accuracy of 3D-printed denture teeth - Haidar Alalawi; Faisal D. Al-Qarni; Mohammed M. Gad (Elsevier, 2023)
Objective: This in vitro study compares the accuracy and trueness of various 3D-printed denture teeth. Methods: A total of 30 specimens were created using various 3D-printed resins, 10 each using Asiga DentaTOOTH resin (Asiga, Australia), Formlabs Denture Teeth Resin (Formlabs GmbH, Germany), and NextDent C&B MFH (Micro Filled Hybrid) resin (Nextdent B.V., Netherlands), respectively. A prefabricated mandibular first molar was scanned using a desktop laser scanner (E3, 3Shape A/S) to create a standard tessellation language file, which served as a "reference tooth" scan. That file was sent to each corresponding printer for printing according to manufacturer recommendations. The printed teeth were scanned with an intraoral scanner (TRIOS 3, 3shape, Copenhagen, Denmark). Trueness and precision were assessed using 3D morphometric analysis software (Geomagic Control X, 3D Systems, Rock Hill, SC, USA). One-way ANOVA was used to analyze the data (α = 0.05). Root mean square error and mean deviations were also calculated. Data analysis was carried out using SPSS (IBM Corp., New York, NY, USA) software. One-way ANOVA with Tukey's post hoc analysis was used. P-values of<0.05 were regarded as statistically significant. Results: The overall trueness of teeth followed a similar pattern, with the highest trueness recorded with NextDent specimens, while ASIGA specimens had the lowest. When precision was assessed, there were significant differences in occlusal areas between FormLabs and NextDent specimens (p = 0.01) and between FormLabs and ASIGA specimens (p = 0.002). However, ASIGA and NextDent did not differ from one another (p = 0.9). The precision analysis shows that all tested groups had similar values, with no significant differences among them. Conclusion: The trueness values of the tested printing systems varied, although the precision values were similar. All evaluated printing systems achieved printing accuracy falling within the clinically acceptable range.